Composite Materials and Types of Machining - Mohamed, Prof. Ts. Dr. Saiful Bahri; Ab Rashid, Prof. Madya Dr. Radzuwan; Muhamad @ Mohd Saufi, Ts. Dr. Martini (Springer Verlag, 2019)
A composite material is a composition of two or more constituent materials to form an overall structure which significantly better in terms of mechanical or chemical properties than the sum of individual material.